ANALISIS PENGENDALIAN INTERNAL PIUTANG USAHA UNTUK MEMINIMALKAN PIUTANG TAK TERTAGIH PT XYZ - Ariyati Ariyati (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2019)
This research aims to identify and analyze the system of internal control ofaccounts receivable on PT. XYZ to minimize bad debt expense. The researchapproach used is a descriptive that is used by collecting, compiling, classifyingdata that they can find out the clear events regarding the problems that have beenresearch. Operational definition used by the internal control system of accountsreceivable and bad debt expense. The type of data used is qualitative. Primaryand secondary data sources. Data collection techniques used are documentationand interviews. Data analysis techniques used are descriptive. The results of theresearch show that the internal control of accounts receivable PT. XYZ has notbeen done effectively. this is seen from the activity of controlling trade receivablesin the collection results that often pass from the due date. PT. XYZ do not haveinternal audits and have not been effective in using accounting methods to themaximum in an effort to minimize bad debt expense.